Evaluation of Drug Addicts Rate with Environmental Components Study in Terengganu, Malaysia - Ekhwan Toriman, Mohd; Khairul Amri Kamarudin, Mohd; Atikah Mohd Adanan, Nur; Haron, Norfatihah; Nurul Izatiumira Syed Omar, Sharifah; Nur Ain Syazwani Wan Mohamad Zailan, Wan; Amira Shafiqah Zulkifli, Nor; Nor Fazillah Abdullah, Siti (International Journal of Engineering and Technology, 2018)
The evolution of drug addict’s rate is significantly increase in Malaysia and it's became a chronic problem among the society. The number of drug addiction cases in Malaysia is contributed by the number of drug addicts involving all the states including Terengganu. The aim of this study is to evaluation the rate of drug addicts according to several environmental components which affects the increment of drug addiction in Terengganu. In this study, the Descriptive Statistics Analysis using XLSTAT has been use to describe the result. The results indicate there are five factors that involve with drug influence including peer influence, curiosity, depression, fun and enduring pain or body defense and the major factors influencing the involvement of drug addicts into this problem is peer influence. Therefore, the stakeholder involved could put an effort to reduce the drug addicts’ rate through proving an effective plan. This study suggested all parties need to know the tremendous drug problem not only in Terengganu but also in Malaysia. This is so that the problem of drug can be reduced and make Malaysia a nation free from drug debris that can endanger everyone.